Supply Chain and Inter-Cost (Cost Management Across Organizational Boundaries) Using ERP System in Diwaniyah Textile Factory - Maytham Azeez Khzaee (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
ERP software has become an essential tool for managing and organizing vast amounts of data within institutions, especially with the rise of big data concepts. As a relatively new innovation, ERP falls under the umbrella of digital transformations shaping the modern world. These systems, along with their associated applications, offer capabilities that facilitate integration and coordination among departments and processes within organizations. This, in turn, supports better strategic decision-making. Additionally, ERP systems play a crucial role in enhancing production processes and improving customer interaction, provided that the technology and the data it generates are utilized effectively